Adopt best practices for emergency management planning for students traveling abroad. Issue 5 (September 2017) - Sutton, Halley
Abstract : Emergency management on your campus is a difficult enough task, but adding in emergency management for students who travel abroad complicates your responsibilities as a campus safety officer even further. "Education Abroad: Effective Crisis Management" a white paper written by Joseph L. Brockington and released by NAFSA: Association of International Educators, outlines best practices for developing an emergency response plan and policy for students, along with tips for dealing with media and resources for staying up‐to‐date on worldwide safety concerns.